NONINVASIVE METHODS ASSESSMENT BLOOD FLOW IN ANTERIOR SEGMENT AND CLINICAL APPLICATION PERSPECTIVE - T. N. Kiseleva; V. I. Kotelin; O. A. Losanova; K. V. Lugovkina (Oftalʹmologiâ, 2017)
The literature review contains information on the anatomical and physiological features of the vessels of the conjunctiva, iris, ciliary body. There are data on the development and application of new non-invasive methods for the study of hemodynamics in the microvessels of anterior eye segment. To study the blood flow of the anterior segment of the eye, biomycroscopy, photography and videobiomicroscopy, television biomicroscopy of vessels, darkfield visualization, application fluorescence angiography, photoacoustic angiography, orthogonal polarization spectroscopy, laser Doppler flowmetry and OCT-angiography were used in recent years. These methods allow to determine the qualitative and quantitative characteristics of conjunctiva, iris, ciliary body microcirculation. They are highly informative for assess of various drugs effect on the vascular eye system. Investigation of hemodynamics in the eye microvessels is necessary for a fundamental approach to the study of the pathophysiology of systemic circulatory pathologies (with arterial hypertension, diabetes, etc.) and changes in regional blood flow in organ of vision disease. Monitoring of anterior segment microcirculation in clinical practice makes possible to monitor the effectiveness of drug and surgical treatment.